Encapsulation of l-valine, d-leucine and d-methionine by cucurbit[8]uril. Issue 5 (12th January 2022) - Zhang, Zeng-Hui; Lin, Rui-Lian; Yu, Xiang-Yun; Chen, Li-Xia; Tao, Zhu; Xiao, Xin; Wei, Gang; Redshaw, Carl; Liu, Jing-Xin
Abstract : The binding interactions of cucurbit[8]uril (Q[8]) with l -valine, d -leucine, and d -methionine, both in aqueous solution and solid state, have been studied by 1 H NMR spectroscopy and X-ray crystallography. Abstract : The binding interactions of cucurbit[8]uril (Q[8]) with l -valine, d -leucine, and d -methionine, both in aqueous solution and solid state, have been studied by 1 H NMR spectroscopy and X-ray crystallography. 1 H NMR data indicate that Q[8] can encapsulate these three kinds of amino acids in aqueous solution. X-ray crystallography reveals how the Q[8] binds with the amino acids to form inclusion complexes l -Val2 @Q[8], d -Leu2 @Q[8], and d -Met2 @Q[8] through host-guest interactions. It was also found that the deformation degree of the Q[8] host is related to the molecular size of the encapsulated guests.